Biological Markers of Stress in Pregnancy: Associations with Chronic Placental Inflammation at Delivery - Ernst, Linda M.; Grobman, William A.; Wolfe, Kaitlin; Huang, Michael H.; Mcdade, Thomas W.; Holl, Jane L.; Borders, Ann E.B. (American Journal of Perinatology, 2013)
Objective To estimate the association between biomarkers of chronic stress during pregnancy and chronic placental inflammation.Study Design African-American and Caucasian pregnant women were recruited between May 2008 and July 2009. Blood samples were collected between 14 and 226/7 weeks and between 28 and 326/7 weeks of gestation. Samples were analyzed for serum C-reactive protein (CRP), Epstein-Barr virus (EBV) antibody, corticotropin-releasing hormone (CRH), and adrenocorticotropic hormone (ACTH). Placentas were collected at delivery and evaluated for chronic inflammation.Results Placentas were available from 88 of the 112 women enrolled in the study. EBV antibody levels were significantly higher during both the second and third trimester in women whose placentas demonstrated chronic villitis. CRP values also were significantly higher during the third trimester when chronic villitis was present. No association between placental chronic inflammation and CRH or ACTH was found.Conclusion Chronic placental inflammation is associated with elevated serum EBV antibody and CRP levels during pregnancy.
Keywords: chronic inflammation; placenta; stress; biomarkers; chronic villitis